Responding to new Imageries in African indigenous Spiritualties - Nweke, Kizito Chinedu (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
As a result of rash and incorrect assumptions, African spiritualities have been adulterated, bastardized, and multiplied. Academic studies in African spiritualities "were mostly conducted by Europeans and Americans who were extremely biased and primarily focused their scholarship on comparing African religion with Christianity and Islam. I will approach the new images of African spiritualities from two perspectives: the conflict between religion and spirituality, and the demonization of African spiritualities. The goal of this study is to present a new picture of African spirituality from two perspectives: the tension between religion and spirituality, and the demonization of African spirituality. The study's findings indicate that there is a complicated phenomenon that disfigures African spirituality. In both indigenous spirituality in Africa, and in spirituality created by Africans in the diaspora, the problem of portraying demonic African styles and perspectives in expressing mundane and non-mundane realities seems accepted. There are three aspects in analyzing this: historical-racial, media-social, and ideological. These aspects cross over on the point of African religion versus spiritualities.